Model for Working Capital Management of Micro, Small and Medium Enterprises in Indonesia by Using Multiple Objective Stochastic Programming - Gultom, Parapat; Widyasari, Rina; Suyanto,; Marpaung, Jonathan Liviera (Journal of Research in Mathematics Trends and Technology, 2023)
Micro, small and medium enterprises (MSME) have a big influence for the economy in Indonesia. But almost of this company don’t have an optimal working capital management because less knowledge and limitation of financial not only from the owner but also financial credit from bank. Working capital management plays an important role in the success or failure of a company its business activities. To achieve optimal use of working capital management managers the company must accurately control the trade-off between profitability and liquidity. The purpose of this research is to develop a model of working capital management where the sales are under uncertainty and the company has a limit financial. This study was tested using multiple linear regression analysis to see the correlation between profitability and liquidity with x1, x2, x3, x4, and x5 then find optimal solution by stochastic multi objective programming because we consider that sales is in under certainty. The main variables used in the analysis of return on assets to measure profitability, receivable turnover to measure liquidity, inventory turnover, accounts payable days, cash conversion. The results showed that account payable, inventory turnover, and cash turn over have a positive correlation for liquidity but inventory turnover and cash turnover have negative correlation to profitability.